2015
DOI: 10.7314/apjcp.2014.15.23.10071
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Providing Cervical Cancer Prevention Programs In Iran: A Qualitative Study

Abstract: Background: Cervical cancer has become a major public health problem worldwide. Iran, like other developing countries, is facing a number of challenges in managing the disease. This qualitative study documents challenges encountered in cervical cancer preventing programs in Iran. Materials and Methods: In-depth interviews were conducted with 28 participants including eleven patients with cervical cancer, three gynecologic oncologists, five specialists in Obstetrics and Gynecology, five midwives, three health c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 19 publications
(22 reference statements)
4
32
0
Order By: Relevance
“…Thirdly, with regard to cues to action, our respondents disliked discussing and thinking about cervical cancer and their existing symptoms, due to local beliefs about the consequences of such thinking and discussions, a finding reported in other studies (24,27,52,59). Consequently, receiving a cue to act as a result of discussions with others is rare in Iran.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Thirdly, with regard to cues to action, our respondents disliked discussing and thinking about cervical cancer and their existing symptoms, due to local beliefs about the consequences of such thinking and discussions, a finding reported in other studies (24,27,52,59). Consequently, receiving a cue to act as a result of discussions with others is rare in Iran.…”
Section: Discussionmentioning
confidence: 54%
“…Several factors have been found to be associated with low attendance of cervical cancer screening in various countries. Some of these pertain to socio-demographic factors, such as access to services and financial issues (24,25), lack of advice from a health care provider (HCP) (20,25,26), and social and cultural barriers (24,27,28). Others are related to women's knowledge regarding the existence of HPV infection-and cervical cancer screening programs (26,(29)(30)(31)(32), factors influencing the awareness of the need to be screened (33,34), misconceptions about suseptibility to CC (34), and contextual cues such as cancer in the family (20).…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, with regard to cues to action, our respondents disliked discussing and thinking about cervical cancer and their existing symptoms, due to local beliefs about the consequences of such thinking and discussions, a nding reported in other studies (24,27,53,60). Consequently, receiving a cue to act as a result of discussions with others is rare in Iran.…”
Section: Discussionmentioning
confidence: 60%
“…Our stage correlation has shown that early staged cancers of the uterine cervix are more likely to be detected in educated patients irrespective of their levels of educational qualification. Low level of knowledge in females poses a challenge in prevention strategies for uterine cervix cancer (Bayrami et al, 2014). There might be associated sociodemographic contributing factors like compliance and adherence to treatment protocol, personal hygiene and self care, nutritional status etc in the improvement of median and overall survival in patients with higher educational qualifications in our population, which warrants further investigation.…”
Section: 3121 Educational Levels and Survival In Indian Patients Witmentioning
confidence: 99%